The multiplex interactions and molecular mechanism on genotoxicity induced by formaldehyde and acrolein mixtures on human bronchial epithelial BEAS-2B cells - Sen Zhang (Environment International, 2020)
Aldehydes are common air pollutants with carcinogenicity. Genotoxicity of single aldehyde has been studied well, but the combined genotoxicity is rarely known. Here, we evaluated the combined genotoxicity of formaldehyde and acrolein on BEAS-2B cells in terms of DNA strands breakage, chromosome damage and gene mutation below subcytotoxic concentrations covering smoking-related concentrations. Meanwhile, the molecular mechanism was investigated further based on oxidative stress, DNA-protein crosslinks (DPCs), cell cycle and DNA damage-repair pathway. Co-exposure to formaldehyde and acrolein mixtures showed significantly synergistic interaction on DNA strands breakage and chromosome damage in a concentration/time-dependent manner, while antagonism was shown on the late genotoxic endpoints (e.g. cytoplasmic block micronucleus (CBMN) and HPRT gene mutation). Moreover, formaldehyde synergistically potentiated acrolein-induced S-phase arrest, inhibition of DNA repair and up-regulation of genes related to cell stress, which conversely strengtherned mixture-induced DNA/chromosome damage and finally resulted in antagonism on late genotoxic events. Additionally, formaldehyde-induced DNA damage mainly resulted from the direct covalent bonding (e.g. DPCs), while acrolein-induced DNA damage mainly generated from oxidative damage (e.g. oxidative stress), which dominated the synergistic DNA strand breakage induced by mixtures. Summarily, aldehyde mixtures (formaldehyde and acrolein) induced multiplex combined genotoxicity on BEAS-2B cells even at smoking-related concentrations, which was dependent on genotoxic endpoints and closely related to that formaldehyde potentiated acrolein-induced cell stress, S-phase arrest and inhibition of DNA repair. So prolonged exposure to aldehyde mixtures may have a more serious risk to respiratory system in animal and human than the expectation based on the toxicity of single aldehyde even at environmentally relevant concentrations.